Data for "Scenario Planning for a Circular Future: Peterborough Context" report - Trovato, A.; Tierno, A.; Hutchinson, B.; Abu-Bakar, H.; Nkudzi, M.; Singam, V. (Cranfield University, 2018)
Video: the motion infographic used as an engagement tool for local businesses within Peterborough (UK) to bridge the gap between interest and action within circular economy. Spreadsheet: break down of data and calculations used for the scenario foresighting.
Keywords: circular economy'; 'scenario foresight'; 'peterborough'; 'Environmental Sciences not elsewhere classified'